Absolute distance measurement by dual-comb interferometry with multi-channel digital lock-in phase detection. (1st July 2015) - Yang, Ruitao; Pollinger, Florian; Meiners-Hagen, Karl; Krystek, Michael; Tan, Jiubin; Bosse, Harald
Abstract: We present a dual-comb-based heterodyne multi-wavelength absolute interferometer capable of long distance measurements. The phase information of the various comb modes is extracted in parallel by a multi-channel digital lock-in phase detection scheme. Several synthetic wavelengths of the same order are constructed and the corresponding phases are averaged to deduce the absolute lengths with significantly reduced uncertainty. Comparison experiments with an incremental HeNe reference interferometer show a combined relative measurement uncertainty of 5.3 × 10 −7 at a measurement distance of 20 m. Combining the advantage of synthetic wavelength interferometry and dual-comb interferometry, our compact and simple approach provides sufficient precision for many industrial applications.